Crystal Structure of N‐(2‐Hydroxynapthylidene)‐L‐isoleucinyl‐4, 6‐O‐ethylidene‐β‐D‐glucopyranosylamine and an Insight from Experimental and Theoretical Calculations. Issue 3 (18th December 2022) - Mishra, Santosh K.; Parikh, Anuvasita; Rangan, Krishnan; Sah, Ajay K.
Abstract: Dimethyl sulfoxide solution of N ‐(2‐hydroxynapthylidene)‐L‐isoleucinyl‐4, 6‐ O ‐ethylidene‐β‐D‐glucopyranosylamine (L1 ) affords single crystals of its ketoenamine configuration. The noncovalent intermolecular interactions present in the molecules have been explored by Hirshfeld surface analysis and 2D fingerprint plots generated using crystallographic data. The structural parameters of L1 in both the tautomeric forms (ketoenamine and phenolimine) at ground states have been optimized using Hartree–Fock and density functional theory calculations in gaseous and solution phases. The Fourier transform infrared, nuclear magnetic resonance, and UV–visible spectra of this molecule have been compared with the theoretically calculated data of both the tautomeric forms. Additionally, Mulliken population analysis, molecular electrostatic potential, and natural bond order analysis provide a better understanding of charge distribution, presence of electrophilic/nucleophilic sites, and intramolecular charge transfer, respectively, in the molecule. Abstract : The solution‐phase structural analysis of N ‐(2‐hydroxynapthylidene)‐L‐isoleucinyl‐4, 6‐ O ‐ethylidene‐β‐D‐glucopyranosylamine (L1 ) has been explored using nuclear magnetic resonance and UV–visible absorption spectroscopy, while the solid‐state molecular structure has been established by Fourier transform infrared and single crystal X‐ray diffraction studies. Theoretical calculations have also been performed to establish the noncovalent intermolecular interactions and quantum chemical descriptors for ketoenamine and phenolimine form of L1 .